Changes induced in mouse lipid metabolism by simultaneous impact of antisense oligonucleotide derivatives to apoB, PCSK9, and apoCIII mRNAs - S. I. Oshevski; Y. I. Ragino; E. V. Kashtanova; Y. V. Polonskaya; E. M. Stakhneva; V. P. Nikolin; N. A. Popova; N. A. Kolchanov; M. I. Voevoda (Вавиловский журнал генетики и селекции)
Development of new drugs able to decrease the level of “bad” cholesterol, in particular, based on antisense oligonucleotide derivatives (ASOs), remains relevant for the patients with familial hypercholesterolemia and/or intolerant to statins. The goal of the work was to assess the changes in the lipid metabolism caused by variants of joint impact of the ASOs targeted to the mRNAs of its key genes: apoB, PCSK9, and apoCIII. Female C57BL/6J mice; nuclease-protected 13- and 20-nucleotide ASOs, and standard protocols for quantification of lipoproteins (HDL CHL, non-HDL CHL, and total CHL) and ALT in the blood serum were used in the work. The following combinations of ASOs were four times injected to the mouse caudal vein: 1) ASO to apoB, 2) ASO to apoCIII, 3) ASO to apoB and ASO to PCSK9, 4) ASO to apoB, ASO to PCSK9, and ASO to apoCIII, 5) ASO to apoB (three doses), ASO to PCSK9, and ASO to apoCIII (two doses), 6) ASO to PCSK9 and (ASO to apoCIII – only in the fourth administration). Triple weekly administration of these ASO combinations resulted in a decrease in non-HDL CHL by 25, 16, 35, 47, 60, and 7 %, respectively, as compared with the control and 1.8-, 1.5-, 1.9-, 2.4-, 3.1, and 1.24-fold higher HDL CHL/ non-HDL CHL ratio. The subsequent ASO injection with concurrent switching to a high-fat diet after 1 week resulted in a decrease in the non-HDL CHL by 28, 2, 28, 70, 33, and 49 % for ASOs (1–6), respectively, as compared with the control; the HDL CHL/non-HDL CHL ratio was 1.5-, 1.1-, 2-, 3.7-, 1.9-, and 2-fold better. The ALT concentration for all ASO combinations remained within the norm for the control animals, demonstrating the absence of any hepatotoxic effect. The best efficiency of ASOs requires selection of concentrations for single ASOs and their combinations as well as of the order and timing of administration. Thus, a new antisense approach is proposed.